Living Hadith of the Lazismu Movement and Its Influence on Indonesian Society - Rohmansyah Rohmansyah; Mukhlis Rahmanto; Mahli Zainuddin; Anidah Robani (Religia, 2023)
Poverty is an essential issue for Muhammadiyah as a socio-religious and social organization in Indonesia. Poverty is caused by ignorance and underdevelopment and has occurred from the past to the present. To solve this problem, Muhammadiyah through Lazismu takes social action based on hadith. Muhammadiyah revives and implements hadith in the form of genuine assistance. This paper aimed to address the problem of poverty through Lazismu based on the hadith of social action. This research used qualitative scientific methods based on field research through observation, interviews, and library research. The results of this study indicated that the social activities carried out by Lazismu are a manifestation of tajdid/renewal and efforts to revive hadiths. The Lazismu assistance program includes direct assistance to the poor, natural disaster relief, educational issues, and the economy. Lazismu has a major influence on the welfare of the Indonesian people, especially the poor and underdeveloped and those affected by disasters. Poor and unemployed people receive productive alms assistance from Lazismu to facilitate their innovation and creativity in creating business opportunities that are able to develop and be sustainable.